Mechanism of integrated teaching of speech competence in Uzbek and English languages in medicine Tashkent Medical Academy (Global Scientific Review, 2022)
This article provides information about speech competence. It is explained about the improvement of speech competence of students in medical higher education institutions and its methods. Pedagogical skills and methods of teaching students at medical higher education institutions were discussed